Adjustment unit price request for prefabrication steel structures works of BRAC University new campus project VO#09 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding adjustment unit price request for prefabrication steel structures works of BRAC University new campus project.